Evaluating the behaviour of Andean Flamingos Phoenicoparrus andinus and James’s Flamingos P. jamesi in captivity: comparing species and flocks using multiple methods - Rose, Paul E. (Wildfowl, 2019)
Behavioural data can offer a useful basis for examining how animals respond to a managed environment. For species with restricted ecological niches and complex behaviour patterns in the wild, such data can ensure that husbandry enables birds in zoological collections to perform key behaviours. Andean Flamingos Phoenicoparrus andinus and James’s Flamingos P. jamesi, for example, are habitat and dietary specialists which live in large flocks and exhibit ritualised group displays in the high montane salt lakes of the Andes Mountains. Both species are uncommon in zoological collections, but are kept at the Wildfowl & Wetlands Trust (WWT) Slimbridge Wetland Centre, UK and at Zoo Berlin, Germany. Data recorded during long-term monitoring flamingos at the WWT were compared with data from a 2-year study undertaken in 2013–2014 at Zoo Berlin, to validate behaviours recorded for these species in collections, to gain a better understanding of their flock social dynamics and time-activity budgets and to assess how activity patterns are influenced by enclosure size, space and social grouping. Observations showed stable partnerships between flamingos at Zoo Berlin, with ties between specific dyads present for both years of the study. Non-random association was significantly predicted by species (within-species bonds significantly more common than between) but not by the sex of the birds. Time-activity budgets were consistent across sites and years and between species, with resting, preening and foraging dominating all activity, although Slimbridge birds were more influenced by prevailing weather conditions. James’s Flamingos were more vocal than Andean Flamingos and displayed more aggression overall at Zoo Berlin. Although Andean Flamingos were more likely to be aggressive towards James’s Flamingos than vice versa, levels of aggression were very low. Both species had preferred areas of occupancy, with Andean Flamingos favouring water and James’s Flamingos the nesting areas, but Andean Flamingos ranged more widely.